2022
DOI: 10.51866/oa.27
|View full text |Cite
|
Sign up to set email alerts
|

Primary care of preputial adhesions in children – a retrospective cohort study

Abstract: Introduction: Aside from religious circumcisions, the indications for circumcision are few. However, in the cultural context, many patients are unnecessarily referred for circumcision for physiological phimosis (adhesions). Due to parental concerns and misperceptions by general practitioners, nonretractile prepuce is one of the most common indications for referral to a paediatric surgeon in many countries. This study aimed to determine whether preputial adhesiolysis successfully managed symptomatic non-retract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The most common cutaneous adverse effects of circumcision included the incomplete removal of the prepuce, the excessive removal of the foreskin, chordee, foreskin adhesion to glans, fistula, inclusion cyst, penile rotation, and trapped penis. 29 , 30 A meta‐analysis revealed that new suture devices had fewer cutaneous complications than traditional surgical circumcision. 31 Urethrocutaneous fistula is a rare but serious side‐effect of circumcision that concerns the parents and children and needs reoperation in most situation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common cutaneous adverse effects of circumcision included the incomplete removal of the prepuce, the excessive removal of the foreskin, chordee, foreskin adhesion to glans, fistula, inclusion cyst, penile rotation, and trapped penis. 29 , 30 A meta‐analysis revealed that new suture devices had fewer cutaneous complications than traditional surgical circumcision. 31 Urethrocutaneous fistula is a rare but serious side‐effect of circumcision that concerns the parents and children and needs reoperation in most situation.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] The original research articles encompass a diverse range of patients and medical conditions of primary care, ranging from screening to complications in chronic diseases and covering all ages from children, adolescence to older age groups. [6][7][8][9][10][11] I hope that MFP will continue to receive support from all our readers, contributors, reviewers and editors for the continuing progress of the journal.…”
mentioning
confidence: 99%